Пусть х - первое число. Уравнение:
6/7 · х + 15 = 45
6/7 · х = 45 - 15
6/7 · х = 30
х = 30 : 6/7
х = 30 · 7/6
х = 5 · 7
х = 35 - первое число
35 : 5/8 = 35 · 8/5 = 7 · 8 = 56 - второе число
3/7 · (56 - 35) = 3/7 · 21 = 3 · 3 = 9 - третье число
35 + 56 + 9 = 100 - сумма трёх чисел (100%)
35 от 100 = 35% от суммы
ответ: 35% от суммы всех трёх чисел составляет первое число.
Пусть х - первое число. Уравнение:
6/7 · х + 15 = 45
6/7 · х = 45 - 15
6/7 · х = 30
х = 30 : 6/7
х = 30 · 7/6
х = 5 · 7
х = 35 - первое число
35 : 5/8 = 35 · 8/5 = 7 · 8 = 56 - второе число
3/7 · (56 - 35) = 3/7 · 21 = 3 · 3 = 9 - третье число
35 + 56 + 9 = 100 - сумма трёх чисел (100%)
35 от 100 = 35% от суммы
ответ: 35% от суммы всех трёх чисел составляет первое число.